2018
DOI: 10.1371/journal.ppat.1007267
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling controls Kaposi's sarcoma-associated herpesvirus reactivation from latency

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is the etiologic agent of three human malignancies, the endothelial cell cancer Kaposi’s sarcoma, and two B cell cancers, Primary Effusion Lymphoma and multicentric Castleman’s disease. KSHV has latent and lytic phases of the viral life cycle, and while both contribute to viral pathogenesis, lytic proteins contribute to KSHV-mediated oncogenesis. Reactivation from latency is driven by the KSHV lytic gene transactivator RTA, and RTA transcription is controlled by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 55 publications
0
38
1
Order By: Relevance
“…KSHV reactivation, and subsequent oncolysis, was only initiated when cells were co-treated with JQ1 and an NF-κB-activating compound (PEP005) (Zhou et al, 2017 ). This is in contrast to reports elsewhere of KSHV reactivation with BET BRDi alone (Chen et al, 2017 ; Hopcraft et al, 2018 ), although the disparity in results may be due to the range of PEL cell and reporter lines used across all of these studies, some of which are also EBV-positive. In a sophisticated study, the Lieberman laboratory resolved the molecular mechanism of BET BRDi-induced KSHV reactivation; using JQ1, they showed that the three-dimensional (3D) looping conformation of the KSHV genome that maintains the expression of latent transcripts (Chen et al, 2013 ) was destabilized such that lytic expression ensued (Chen et al, 2017 ).…”
Section: Bet Bromodomain Inhibition and Gammaherpesvirusescontrasting
confidence: 88%
“…KSHV reactivation, and subsequent oncolysis, was only initiated when cells were co-treated with JQ1 and an NF-κB-activating compound (PEP005) (Zhou et al, 2017 ). This is in contrast to reports elsewhere of KSHV reactivation with BET BRDi alone (Chen et al, 2017 ; Hopcraft et al, 2018 ), although the disparity in results may be due to the range of PEL cell and reporter lines used across all of these studies, some of which are also EBV-positive. In a sophisticated study, the Lieberman laboratory resolved the molecular mechanism of BET BRDi-induced KSHV reactivation; using JQ1, they showed that the three-dimensional (3D) looping conformation of the KSHV genome that maintains the expression of latent transcripts (Chen et al, 2013 ) was destabilized such that lytic expression ensued (Chen et al, 2017 ).…”
Section: Bet Bromodomain Inhibition and Gammaherpesvirusescontrasting
confidence: 88%
“…H3K27me3, H3K9me3, and hypoacetylated histones) [6,7]. The repression of lytic genes during latency can be achieved by various inhibitory epigenetic and transcriptional mechanisms such as DNA methylation [8], Polycomb Repressive Complex 1 (PRC1)-and PRC2-mediated histone modifications [6,7,9], histone deacetylation [10,11,12,13], viral chromosome looping [14,15], and NELF-mediated transcription elongation inhibition [16]. Of the lytic genes, the transcriptional regulation of ORF50, which encodes the viral replication and transcription activator (RTA), has been studied in more detail because of its essential role in the lytic cycle [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that PLK1 inhibition significantly reduces the downstream c-Myc phosphorylation and impairs BRD4 binding to the c-Myc gene inhibiting c-Myc transcription 56 . Our study demonstrated that PLK1 inhibition induced KSHV reactivation involves c-Myc (Fig 5), which further affects the level of H3K27me3 suppressive mark that associates with the repressed transcription of KSHV lytic genes 57 . In this study we successfully delineated that the connection of PLK1 inhibition with c-Myc dysregulation and the subsequent change of histone methylation marks.…”
Section: Discussionmentioning
confidence: 64%